Parental Enriched Environment: A Look Through Key Temporary Windows - Renard, G (John Wiley and Sons Inc, 2023)
Environmental enrichment is a widely used experimental manipulation that physically, cognitively and socially stimulates individuals. It has a great variety of long-term effects at neuroanatomical, neurochemical, and behavioral level; however, the influence of parental environmental enrichment during gestation and pregestation on the development of the offspring and on the mother s behavior has been poorly explored. This article presents a review of the literature from the year 2000 about the effects of maternal and paternal environmental enrichment on the behavioral, endocrine, and neural systems of offspring and parents. Relevant research terms were searched for on the biomedical databases, PubMed, Medline, ScienceDirect, and Google Scholar. The data suggest that paternal/maternal environmental enrichment can profoundly affect the developmental trajectories of offspring through putative epigenetic mechanisms. Environmental enrichment presents as a promising therapeutic tool for human health interventions, especially to counteract the deleterious effects of impoverished and adverse growing conditions. © 2023 British Society for Neuroendocrinology.